IL10 and poly-DL-lactide-[epsilon]-caprolactone conduits in critical size nerve defect bridging - Leibig, Nico; Boyle, Veronika; Kraus, Daniel; Stark, Gerhard Björn; Penna, Vincenzo (Microsurgery, 2016)
Introduction Aim of this study is to evaluate if regeneration in repair of nerve defects can be improved by combination of a poly-dl-lactide-ɛ-caprolactone conduit (PLC) with long-term release of anti-inflammatory Interleukin 10 (IL10), which is known to reduce intraneural scarring in nerve regeneration through its anti-inflammatoric properties. Method Experiments were performed at 30 female Lewis rats. Conduits filled with fibrin (PLC-group n = 10) and fibrin loaded with IL10 (IL10-group n = 10) were compared to autologs nerve grafts (NG-group n = 10) in a 15 mm sciatic nerve gap lesion. Sciatic function index (SFI) and electrophysiological analyses were performed 16 weeks after surgery prior to histological evaluation. In histological analyses total nerve count, total nerve area, myelination index, and N-ratio were measured. Additionally, gastrocnemius muscle was weighed. Results SFI (NG-group:-50.68 7.03%; PLC-group:-56.48 2.30%; IL10-group:-56.54 8.22%) and nerve conduction velocity (NG-group: 92.52 4.64 m/s; PLC-group: 92.77 5.07 m/s; IL10-group: 93.78 3.63 m/s) showed no significant differences after 16 weeks (P > 0.05). Significant higher axon count (17.592 483) were observed in the NG-group compared to PLC- (6.722 553) and IL10-group (6.842 681) (P < 0.001). NG-group had significant highest nerve cross sections (604.214 ±15.217 µm2) as compared to PLC- (245.669 ±28.034 µm2) and IL10-group (244.698 26.772 µm2) (P < 0.001). Comparison of myelination index showed significant higher values for NG-group (0.46 0.02) than PLC- (0.64 0.01) and IL10-group (0.62 0.01) (P < 0.001). N-ratios in PLC-group (0.21 0.01) and IL10-group (0.24 0.01) were lower than in NG-group (0.51 0.03) (P < 0.001). Between PLC- and IL10-group no differences were observed (P > 0.05). Gastrocnemius muscle was heavier in NG-group (0.86 0.21g) as compared to PLC- (0.26 0.05g) and IL-10 group (0.29 0.06 g) (P < 0.05). Conclusion Bridging critical nerve defects through fibrin-filled PLC conduits is possible. Although, autologs nerve graft showed superior histological results. Long-term release of IL10 in the conduit did not improve regeneration of critical nerve defects. © 2015 Wiley Periodicals, Inc. Microsurgery 36:410-416, 2016.